The Right to Be Forgotten and COVID-19: Privacy versus Public Interest - Correia, Mónica; Rego, Guilhermina; Nunes, Rui (Acta Bioethica, 2021)
Recent studies highlight the importance of digital surveillance to gather individual health information due to the global pandemic caused by the new COVID-19 disease. This paper analyses its legal and ethical implications at the interface between the individual right to privacy and the collective inter-ests of public health. We framed the discussion in law, deontology and utilitarianism. The lasted theories and human rights, especially privacy, are crucial in our argument. Health-derived dilemmas and efforts to solve them, especially by information technologies, bioethics and law, exist at these perspectives' interface. In particular, we analysed the intersection between autonomy, the right to privacy, and the so-called ‘right to be forgotten’ in the public health context. In other words, we studied the right to obtain from the controller the erasure of health data – a radical means of control over personal data established in Article 17 of the General Data Protection Regulation (GDPR). Giv-en the lack of specifics regarding collection and re-use of such data under the broad scope of public health purposes, implied consent does not address the issue of proportionality. We highlight legal safeguards’ insufficiency, suggesting applying the ‘right to be forgotten’ according to an ethical in-terpretation.